IMPLEMENTASI POHON PINTAR DALAM PEMBELAJARAN CALISTUNG - Sari, Rospala Hanisah Yukti; Supriadi, Supriadi (PUSAT PENELITIAN DAN PENGABDIAN PADA MASYARAKAT (PPPM) POLITEKNIK NEGERI SAMBAS, 2023)
At the elementary school level, the ability to read, write and count are basic capabilities that must be trained at every level of education. In Law Number 20 of 2003 concerning the National Education System, article 4 paragraph 5, it is stated that a principle in implementing education is to create a culture of reading, writing and arithmetic everywhere for every member of society. The aim of this activity is that there is a change in students' activeness and understanding in learning Calistung using smart tree media. The result of this Community Service activity is that there is an increase in students' understanding and activeness in learning Calistung as well as the creation of a balance between learning and playing, so that without students realizing it, playing is included in learning activities.